Voriconazole Sequestration During Extracorporeal Membrane Oxygenation for Invasive Lung Aspergillosis: A Case Report. Issue 3 (29th March 2021) - Mathieu, Alexandre; Thiboutot, ZoÉ; Ferreira, Victor; Benoit, Patrick; Grandjean Lapierre, Simon; HÉtu, Pierre-Olivier; Halwagi, Antoine
Abstract : The increasing use of extracorporeal membrane oxygenation (ECMO) in critical care introduces new challenges with medication dosing. Voriconazole, a commonly used antifungal and the first-choice agent for the treatment of invasive aspergillosis, is a poorly water-soluble and highly protein-bound drug. Significant sequestration in ECMO circuits can be expected; however, no specific dosing recommendations are available. We report on the therapeutic drug monitoring and clinical evolution of a patient treated with voriconazole for invasive pulmonary aspergillosis while receiving ECMO therapy. Voriconazole trough levels were persistently low (<1 µg/mL) after initiation of ECMO despite additional loading doses and dose increases. Voriconazole dose had to be increased to 6.5 mg/kg three times daily to obtain therapeutic trough levels. The inability to achieve therapeutic levels of voriconazole for a prolonged period (a minimum of 9 days) while undergoing ECMO therapy is believed to have been a significant contributing factor in the patient's fatal outcome. Therapeutic trough levels of voriconazole cannot be guaranteed with standard dosing in patients undergoing ECMO and much higher doses may be necessary. Empirical use of higher doses and/or combination therapy may be reasonable and frequent therapeutic drug monitoring is mandatory.